2013
DOI: 10.1590/s1413-35552012005000091
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation and analysis of the psychometric properties of the lower extremity functional scale (LEFS): LEFS- BRAZIL

Abstract: | Background: There is a lack of questionnaires in Brazilian Portuguese to evaluate patient-reported lower limb function. Objective: To translate, cross-culturally adapt to the Brazilian population, and evaluate the psychometric properties of the Lower Extremity Functional Scale (LEFS). Method: The LEFS was translated by two independent assessors and back-translated to English. Then, the LEFS-Brazil was tested on 20 patients who answered the questionnaire in the cross-cultural adaptation phase. For the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…On the first day of data collection, all the participants filled out a form with name, age, height and weight and marked the items on the VAS-pain (17,18), the Anterior Knee Pain Scale -AKPS) (19), Lysholm Knee Score Scale (20) and the Lower Extremity Functional Scale (LEFS) (21,22). The volunteers were informed about the objectives of the study and agreed to participate by providing their free and informed consent.…”
Section: -Proceduresmentioning
confidence: 99%
“…On the first day of data collection, all the participants filled out a form with name, age, height and weight and marked the items on the VAS-pain (17,18), the Anterior Knee Pain Scale -AKPS) (19), Lysholm Knee Score Scale (20) and the Lower Extremity Functional Scale (LEFS) (21,22). The volunteers were informed about the objectives of the study and agreed to participate by providing their free and informed consent.…”
Section: -Proceduresmentioning
confidence: 99%
“…LEFS by Binkley and translated with relevant modifications to local situations has been found to be feasible, cost effective and clinically relevant in the field and acceptable in the communities. [20][21][22] LEFS initially applied for outpatients was found to be suitable for the inpatients also. 23 Several studies have demonstrated the relevance and advantages of applying two assessment tools simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…The SMFA also had reported psychometric properties specific to ankle fractures and, like the A-FORM, appears relatively new. The LEFS, formed in 1998, has been translated into Portuguese (40), Persian (41), German (42), and, most recently, Finnish (43) for other musculoskeletal injuries such as hip or knee replacements. The LEFS also requires further testing for longer periods, because it has been only used for testing ≤4 weeks after a lower limb injury.…”
Section: Discussionmentioning
confidence: 99%